PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA BENGKEL KARUNIA BAN PAMULANG - Rustam Effendi; Yasin Efendi; Ainun Najib (LPPM Unbaja, 2021)
The use of technology in the company not only supports business processes but also very important on corporate earning. Business ownerhave always pay attention to the development of the existing technology in order to improve their business success. Therefore many companies want to implement the technology edgein every aspect ofits business processes. Karunia Ban machine shop is a trading company that sells a wide range of tires, especially for goods and service fees. Sales transactions that occur on Karunia Ban shop are still being done manually. Companies often find it difficult to know which sales transaction that are for spare parts or for repair services, so we need an information system tosolve the problem. Information systems is expected to optimize the sales in Karunia Ban machine shop. The methodology that we used to analysis and to develop the structured system are using UML (Unified Modelling Laguage). The expected results from this paper is to establisha procedure that describes a system using UML analysis and design a system that runs the system, the draft also produced a web-based sales application using php and my sql.